Malaria and the Sickle Gene: Polymorphism Balance in favour of eradication - Philip Olusola (Medical and Dental Consultants Association of Nigeria, OOUTH Sagamu, 2018)
Evolutionally, the single nucleotide mutation responsible for the sickle haemoglobin gene, (HbS gene) developed from the regions of the world where malaria is holoendemic, leading to the explanation that the mutation is in response to the presence of the malaria parasite. Studies eventually showed that individuals that are heterozygous for the HbS gene are protected from the lethal clinical effects of malaria infection. In other words, malaria confers a survival advantage to carriers of the HbS gene, and this is referred to as balanced polymorphism. On the other hand, malaria infection is associated with significant morbidity and mortality, particularly among children. Unfortunately, lack of success in the effort to eradicate the malaria parasite through the elimination of the Anopheles mosquito or efforts to limit its contact with human being has produced little success, hence the resort to roll back malaria, with the aim of reducing the morbidity and mortality associated with it. Therefore, it is attractive to consider what will happen to the sickle gene if malaria were to be eradicated. That is, the possibility is that the sickle gene may also follow suit since its evolution in the first instance was as a response to malaria., This is the hypothesis being propounded by this article. In that case, rather than shy away from the malaria eradication initiative, it should remain the goal of all malaria programs.